Microspheres targeted with a mesothelin antibody and loaded with doxorubicin reduce tumor volume of human mesotheliomas in xenografts - Macura, Sherrill L (BioMed Central, 2013)
BACKGROUND: Malignant mesotheliomas (MMs) are chemoresistant tumors related to exposure to asbestos fibers. The long latency period of MM (30-40 yrs) and heterogeneity of tumor presentation make MM difficult to diagnose and treat at early stages. Currently approved second-line treatments following surgical resection of MMs include a combination of cisplatin or carboplatin (delivered systemically) and pemetrexed, a folate inhibitor, with or without subsequent radiation. The systemic toxicities of these treatments emphasize the need for more effective, localized treatment regimens. METHODS: Acid-prepared mesoporous silica (APMS) microparticles were loaded with doxorubicin (DOX) and modified externally with a mesothelin (MB) specific antibody before repeated intraperitoneal (IP) injections into a mouse xenograft model of human peritoneal MM. The health/weight of mice, tumor volume/weight, tumor necrosis and cell proliferation were evaluated in tumor-bearing mice receiving saline, DOX high (0.2 mg/kg), DOX low (0.05 mg/kg), APMS-MB, or APMS-MB-DOX (0.05 mg/kg) in saline. RESULTS: Targeted therapy (APMS-MB-DOX at 0.05 mg/kg) was more effective than DOX low (0.05 mg/kg) and less toxic than treatment with DOX high (0.2 mg/kg). It also resulted in the reduction of tumor volume without loss of animal health and weight, and significantly decreased tumor cell proliferation. High pressure liquid chromatography (HPLC) of tumor tissue confirmed that APMS-MB-DOX particles delivered DOX to target tissue. CONCLUSIONS: Data suggest that targeted therapy results in greater chemotherapeutic efficacy with fewer adverse side effects than administration of DOX alone. Targeted microparticles are an attractive option for localized drug delivery.